Temporally integrated single cell RNA sequencing analysis of PBMC from experimental and natural primary human DENV-1 infections. - Adam T Waickman; Heather Friberg; Gregory D Gromowski; Wiriya Rutvisuttinunt; Tao Li; Hayden Siegfried; Kaitlin Victor; Michael K McCracken; Stefan Fernandez; Anon Srikiatkhachorn; Damon Ellison; Richard G Jarman; et al. (PLoS Pathogens)
Dengue human infection studies present an opportunity to address many longstanding questions in the field of flavivirus biology. However, limited data are available on how the immunological and transcriptional response elicited by an attenuated challenge virus compares to that associated with a wild-type DENV infection. To determine the kinetic transcriptional signature associated with experimental primary DENV-1 infection and to assess how closely this profile correlates with the transcriptional signature accompanying natural primary DENV-1 infection, we utilized scRNAseq to analyze PBMC from individuals enrolled in a DENV-1 human challenge study and from individuals experiencing a natural primary DENV-1 infection. While both experimental and natural primary DENV-1 infection resulted in overlapping patterns of inflammatory gene upregulation, natural primary DENV-1 infection was accompanied with a more pronounced suppression in gene products associated with protein translation and mitochondrial function, principally in monocytes. This suggests that the immune response elicited by experimental and natural primary DENV infection are similar, but that natural primary DENV-1 infection has a more pronounced impact on basic cellular processes to induce a multi-layered anti-viral state.